Aplicación del colorante natural de Cúrcuma (Cúrcuma longa Linn) en Pollos Broiler (Broiler ross 308)para mejorar la pigemntación de la piel. - Oñate Haro, Ángela Noemí (2016)
At present, chicken meat is one of the mostly consumed by the Ecuadorian population, not only because itis the most inexpensive and it has a higher percentage of protein that is the reason why consumer seeks in the chicken meat the yellowing coloration which is related to chickens, they are grown at farms. To satisfy this need, we introduced this study with the intention to apply the natural dye from turmeric for feeding Broiler chickens in order to improve skin pigmentation. For experimentation, 25 Broiler chicks were used. They were randomly divided into five treatment groups which included dosages within the parameters of curcumin consumption (2g / kg), weight and nourishment were also monitored according to each stage of development for the management of food portions. Water consumption, weight and color measurement in the lower extremities (most visible) were recorded twice a week, after slaughter and again at the post mortem stage Turmeric dosage 0.5g / kg got higher weight in chickens generating an increase at 94.65% compared to the control and treatment with 1g/kg; without showing any other change thereof. Close monitoring of chickens with a treatment at 1g/kg, showed a higher consumption of water, but it did not influence in their weight. The measurement of color in white treatment resulted at 24%, in treatments at 0.5 and 1 g/kg, 22% and 23% respectively, giving a pale yellow coloration. Color measurement presented a pale color, with a percentage at 24% in white treatment, 0.5 g / kg a percentage at 22 % and in the treatment of 1g / kg a percentage at 23%. Thus, it is concluded that applying natural dye from Curcuma longa Linn turmeric to feed Ross Broiler chicken to improve skin pigmentation did not achieve this goal, but the increased weight of the chicken, fed with turmeric 0.5g / kg contrasting with white treatment and isolated experiments with laying hens a change in the color of egg yolk was detected, so it is suggested to deepen this research.